Effect of repetitive transcranial magnetic stimulation on mood in healthy subjects. (1st January 2016) - Moulier, Virginie; Gaudeau-Bosma, Christian; Isaac, Clémence; Allard, Anne-Camille; Bouaziz, Noomane; Sidhoumi, Djedia; Braha-Zeitoun, Sonia; Benadhira, René; Thomas, Fanny; Januel, Dominique
Abstract : Background: High frequency repetitive transcranial magnetic stimulation (rTMS) of the left dorsolateral prefrontal cortex (DLPFC) has shown significant efficiency in the treatment of resistant depression. However in healthy subjects, the effects of rTMS remain unclear. Objective: Our aim was to determine the impact of 10 sessions of rTMS applied to the DLPFC on mood and emotion recognition in healthy subjects. Design: In a randomised double-blind study, 20 subjects received 10 daily sessions of active (10 Hz frequency) or sham rTMS. The TMS coil was positioned on the left DLPFC through neuronavigation. Several dimensions of mood and emotion processing were assessed at baseline and after rTMS with clinical scales, visual analogue scales (VASs), and the Ekman 60 faces test. Results: The 10 rTMS sessions targeting the DLPFC were well tolerated. No significant difference was found between the active group and the control group for clinical scales and the Ekman 60 faces test. Compared to the control group, the active rTMS group presented a significant improvement in their adaptation to daily life, which was assessed through VAS. Conclusion: This study did not show any deleterious effect on mood and emotion recognition of 10 sessions of rTMS applied on the DLPFC in healthy subjects. This study also suggested a positive effect of rTMS on quality of life.